A participatory ecohealth study of smallholder pig system in upland and lowland of Lao PDR - Inthavong, Phouth; Durr, P.A.; Khamlome, Boualam; Blaszak, Kate; Somoulay, V.; Allen, J.; Gilbert, Jeffrey (Veterinary Public Health Centre for Asia Pacific, 2013)
A cross-sectional study to determine baseline seroprevalence of key pig zoonoses and some of priority pig production diseases and to evaluate public health risks of pig-raising and pork consumption in one upland and one lowland province, Lao PDR. The surveys were conducted in two provinces, Louangphrabang representative of ‘upland’ and Savannaket province for ‘lowland’. The selection of villages is weighted by village human population derived from the 2005 National census and GIS data. Participatory questionnaire development and data storage was enabled by a new web based programme called SurVet. Humans were tested for exposure to Taenia/Cysticercosis, Trichinellosis, Hepatitis E virus and Japanese encephalitis virus (pigs: Trichinella, HEV, JEV, Erysipelas, CSF, FMD and PRRS). The training and field activities were done with integrated transdisciplinary approaches involving district and provincial staff, as well as students. Result: Provisional seroprevalence and relevant odds ratios show that the viral diseases Hepatitis E and Japanese Encephalitis are widespread in both provinces, but that the parasitic diseases cysticercosis and trichinellosis are more sporadic, the latter apparently associated more with educated males of certain ethnicities. There are also results pertaining to pig health diseases and associated management risks. Further potential for multivariate statistical analysis exists. Outputs: Through the identification of the spatial patterning of seroprevalence and risk factors associated with exposure to these diseases, the IEC materials such as posters and brochures on human health and animal health risk reduction have been developed and produced as well as guide future research and policy.